Consumers' preferences for imported rice attributes in Klang Valley, Malaysia - Ibrahim Abubakar, Yah-Ya (2016)
Rice is the most important source of calorie intake for the majority of Malaysians. Rice production has increased over the years, however, about 30-40% of domestic rice demand is imported annually not only to suffice shortfall in supply but to meet the need of consumers for certain varieties not produced locally. Recently, spending on importation has become a marked concern as the country’s rising per capital incomes, consumers phobia-tic health behaviour and need to cater for certain health condition stimulate increase in the demand and consumption of some imported rice varieties rather than quantity proportionally which consequently led to increased importation to satisfy consumers need. In response, the government is investing efforts to restrict importation through the introduction of hybrids with attributes similar to some of the imported varieties. Consumers’ continuous appetite for imported rice varieties with certain quality attributes and government’s efforts to introduce rice varieties with similar attributes to reduce the cost of importation make it a priority to explore consumers’ preferences for alternative intrinsic and extrinsic attributes of imported rice varieties and willingness to pay for the preferred attributes. This study employed conjoint analysis to determine the relative importance of each attribute and the value consumers attached to each level of attributes. In total, 500 respondents were interviewed via structured questionnaire consisting of combinations of attribute levels and consumers were asked to provide a rating response from 1-10 (1 = least preferred; 10 = most preferred) to indicate their preferences for a particular combination. Ordinary least square regression was used to reveal consumers’ preferences and the magnitude of the coefficients determine the value consumers attach to each attribute. The results showed that price is the most important factor for both intrinsic and extrinsic attributes. For intrinsic attributes, texture is the most important attribute with non-sticky level preferred over the sticky, followed by grain size (long grain is most preferred, followed by medium grain and short grain is least preferred), followed by taste (tasteful preferred over plain taste), followed by aroma (aromatic preferred over non-aromatic) and colour is the least important (creamy white preferred less to white). For non-price extrinsic rice attributes, county of origin is the most important (rice from India-Pakistan is less preferred to rice from Vietnam-Cambodia, and rice from Thailand is most preferred), followed by environmental concern (organic preferred to conventional), followed by packaging (standard packaged preferred to loosely packaged), followed by nutritional value (rice with high fiber, vitamins and minerals is preferred to rice with minimum fiber, vitamins, and minerals) and quantity is the least important attribute (10kg preferred less to 5kg). The result of the willingness to pay for non-price intrinsic attributes showed that consumers are willing to pay more per kg for texture (stickiness), taste (tasteful), aroma (aromatic), and less per kg for colour (creamy white), while for grain size, respondents are willing to pay more per kg for medium grain and long grain. The result of the willingness to pay for non-price extrinsic attributes also showed that respondents are willing to pay more per kg for environmental concern (organic), nutritional value (high fiber, vitamins and minerals), packaging (standard packaged), and less per kg for quantity (10kg), while for country of origin, respondents are willing to pay less per kg for rice from Vietnam-Cambodia and rice from India-Pakistan. This study revealed that introducing certain attributes such as aroma, longer grain, organic, better texture and others will go a long way in meeting emerging consumer need, reduce importation and subsequently improve farmers’ income as consumers are willing to pay for these attributes. Thus, the government should improve its effort in motivating farmers and other bodies involved in the hybrid introduction in making it a huge success. Also, consumer preference for extrinsic attributes such as environmental concern and nutritional value showed that consumers are now becoming more concerned about their health. That is, with proper marketing strategy, patronages of organic and brown/undermilled rice will likely increase as these attributes were clearly desired by consumers.